Investigation on evaporation characteristics of ethanol in annular pool with different liquid layer depths at low pressures. (April 2022) - Guo, Rui-Feng; Zhang, Li; Mo, Dong-Ming; Wu, Chun-Mei; Li, You-Rong
Highlights: Evaporation characteristics of ethanol are studied by experiment and simulation. 3D oscillatory flow in liquid phase is observed at the ethanol depth more than 7 mm. The petal-like pattern below the evaporation interface is examined. The flow destabilization mechanism in the deep pool are revealed. The influence factors of the interface temperature discontinuity are summarized. Abstract: In order to understand the energy transfer process and non-equilibrium effect during ethanol evaporation in its own pure vapor at low pressures, a series of the experimental measurements and numerical simulations are conducted in an annular pool at different liquid layer depths. The results show that the interface temperature of vapor side is higher than that of liquid side when ethanol evaporates in its own pure vapor at low pressures, and the magnitude of interface temperature discontinuity decreases with the increase of liquid layer depth. There are two vortexes below the evaporation interface because of the large radial temperature gradients on the free surface near the cylinders and the buoyancy effect. With the increase of the liquid layer depth, the flow is enhanced and the average evaporation rate increases. In this case, the flow destabilizes from steady state to three-dimensional oscillatory state due to the lag between the variations of velocity and flow resistance, and the petal-like pattern can be clearly observed below the liquid-vapor interface. The evaporation flux near the inner and outer cylinders is much larger than that in the middle region; most of the latent heat required for evaporation is transferred to the interface near the cylinders by thermal convection and the conduction.